Status of inheritance for heirs who take their own share: A case study in Mattoanging village - Tarmizi Tarmizi; Asni Zubair (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to determine the cause of the heirs in Mattoanging Village to take their own share and to find out the law of taking their own share of the inheritance and their ownership status according to Islamic law. This research is qualitative research through a normative sociological and theological approach. The data were obtained through observation and interviews with the community in Mattoanging Village, community leaders and religious leaders with broad understanding of Islamic law determined through purposive sampling. The results showed that several heirs in Mattoanging Village took their own share because the inheritance was not distributed after the heir died, no one regulates the distribution of inheritance, there are heirs who use a lot of the heir's property during his life, the person who divides the inheritance is the eldest child and there are heirs who are greedy in taking part. The law takes its own share of the inheritance according to the agreement of each heir. If the other heirs agree, then it is permissible. However, if the other heirs do not agree, then it is prohibited. Likewise with the ownership status which adjusts to the law of taking it, namely if the law is allowed, then the ownership status is not in doubt so that the assets taken may be used and if the law of taking it is unlawful, then the ownership status is also unlawful.